The Museum is not transparent: Engaging the museum in examination of its own role in the production of history - Harris, Jennifer (Museo Nacional Estancia Jesuitica de Alta Gracia y Casa del Virrey Liniers on behalf of ICOFOM, 2006)
Contemporary museology is attempting to wrest the museum from its role of transparent presenter of history. In this role the museum has assumed itself to have an apolitical position as it has displayed, exhibited and explained objects from the past without taking into account its own complicity in history. The acts of collecting, choosing and displaying artefacts have not been regarded as historic, moral and political. The institution of the museum has regarded itself as transparent, simply a window onto history.